Economic Risk and Stock Market Development: Evidence from Indonesia Stock Exchange - Elmira Siska; Oyyappan Duraipandi (Proceeding of The International Conference on Economics and Business, 2023)
The main objective of current research is to examine the long-run relationship between several economic risk factors which include the exchange rate, rates of interest, inflation, and the stock market capitalization in Indonesia. This study utilized secondary data from the first quarter of 2000 until the fourth quarter of 2020. This study employs a quantitative research design with a descriptive approach. Before processing the data using the Johansen Cointegration test and Vector Error Correction Model (VECM), the stationary of the data was checked by employing the Ng-Perron unit root test. The Eviews-10 program is used to process the data. Ng-Perron unit root test indicated that the time series is stationary at the first difference. Results of the Johansen Cointegration test confirmed that there is a long-term relationship between economic risk which consists of the USD exchange rate against the Rupiah, interest rates, inflation figures, and stock market capitalization. The VECM results indicate that this economic risk indicator has a negative effect on the development of the capital market in Indonesia. The study recommends that the government and policy maker should implement economic risk mitigation through monetary policy instruments to enhance the Indonesia capital market development